Blastocystosis: epidemiology and clinical presentation (Information letter) - Kyrychenko, Igor; Biriukov, Mykhailo; Pokhil, Sergiy; Tymchenko, Olena (Annals of Mechnikov's Institute, 2025)
Blastocystosis is a human disease caused by the protozoan of the genus Blastocystis, which colonize the intestinal tract and, under certain conditions, cause its functional and pathomorphological disorders. Risk factors for infection with the parasite include contact with water contaminated with feces or with infected animals and people, consumption of contaminated food, and failure to observe personal hygiene and sanitation rules. In Ukraine, the prevalence of Blastocystis sp. infestations reaches 5.2–20.1% among the civilian population and 5.5–11.8% among military personnel and is close to the level of similar indicators in developed countries of Europe and the world. In 50–80% of people infected with Blastocystis sp., a manifest – clinically expressed course of the invasion is observed. Blastocystosis affects people with weakened immunity (more often) and with normal immunocompetent status (less often). The typical clinical form of blastocystosis is manifested by symptoms of gastrointestinal disorders: diarrhea, abdominal pain or cramps, bloating, constipation or stool instability, belching, nausea, flatulence, anorexia, uncontrolled weight loss, etc. In the atypical form of blastocystosis, symptoms of skin lesions (urticaria, itching) and joints (discomfort or aching pain) predominate. The most common complications of blastocystosis are the development of protein-energy malnutrition, irritable bowel syndrome, dysbacteriosis, severe forms of urticaria and persistent arthralgia, exacerbation of atopic dermatitis and arthritis, as well as the formation of long-term neurological and cognitive disorders. Differential diagnosis of blastocystosis must be carried out with infectious, inflammatory and autoimmune intestinal diseases.